Piezoelectricity of (K, Na)(Nb, Sb)O3–SrZrO3(Bi, Ag)ZrO3 piezoceramics and their application in planar-type actuators. Issue 46 (16th November 2021) - Go, Su-Hwan; Eum, Jae-Min; Kim, Dae-Su; Chae, Seok-Jun; Kim, Sun-Woo; Kim, Eun-Ji; Chae, Yeon-Gyeong; Woo, Jong-Un; Nahm, Sahn
Abstract : The KNNS–0.01SZ–0.03BAZ piezoceramic exhibited a large d 33 of 650 pC/N because of the presence of a TE–O–R multi-structure and nanodomains. A planar-type KNNS–0.01SZ–0.03BAZ thick-film actuator showed excellent actuating properties. Abstract : A Fe2 O3 –added 0.96(K0.5 Na0.5 )(Nb0.94 Sb0.06 )–0.01SrZrO3 –0.03(BiAg)ZrO3 [KNNS–0.01SZ–0.03BAZ] piezoceramic was well densified at 1090 °C. It exhibited a large piezoelectric charge constant ( d 33 ) of 650 pC/N, which is close to the largest d 33 value reported in the literature. This sample has a tetragonal–orthorhombic–rhombohedral (T–O–R) structure, in which each structure has a similar proportion. Moreover, nanodomains (2 nm × 15 nm) with a low domain boundary energy were found in this sample, which exhibited relaxor properties. Therefore, the presence of a T–O–R multi-structure and nanodomains is responsible for the large d 33 value of this sample. A KNNS–0.01SZ–0.03BAZ thick film was synthesized, and it also had a T–O–R multi-structure with a large d 33 (630 pC/N). A planar-type actuator was produced using this thick film, and this actuator exhibited large acceleration (335 G at 120 V mm −1 ) and displacement (231 μm at 120 V mm −1 ). Hence, the KNNS–0.01SZ–0.03BAZ thick film is a good candidate for lead-free piezoelectric actuators.